1998
DOI: 10.3354/meps167155
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of patterns of colonization by mussels (Mytilus trossulus, M. edulis) on a wave-exposed rocky shore

Abstract: Colonization rates of mussels (Mytilus trossulus and M. edulis) were measured on natural substrata in tidepools and on emergent rock in recently ice-scoured and non-scoured regions of a rocky shore near Halifax, Nova Scotia, Canada. The relative importance of initial settlement/colonization, compared to subsequent dispersal and mortality, in determining the distribution and abundance of mussels was examined by comparing patterns and rates of mussel colonization at sampling intervals of days to months over a 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 25 publications
4
23
1
Order By: Relevance
“…For sedentary marine species with planktonic larvae, settlement is a major process, regulating the dynamics and structure of benthic populations (Hunt & Scheibling 1998, Balch & Scheibling 2000 and acting as a bridge between dispersal and recruitment. In fact, intertidal community structure and population dynamics are strongly affected by the arrival of larvae on the shore, as settlement rates may determine the final spatial variation of adults .…”
Section: Introductionmentioning
confidence: 99%
“…For sedentary marine species with planktonic larvae, settlement is a major process, regulating the dynamics and structure of benthic populations (Hunt & Scheibling 1998, Balch & Scheibling 2000 and acting as a bridge between dispersal and recruitment. In fact, intertidal community structure and population dynamics are strongly affected by the arrival of larvae on the shore, as settlement rates may determine the final spatial variation of adults .…”
Section: Introductionmentioning
confidence: 99%
“…Among all marked individuals, many remained within the confines of the 50 × 50 cm sites -at most, displaced 5 to 15 cm from the transplant. Active crawling behaviour (Schneider et al 2005) generally takes place within a few centimetres and usually occurs on a time scale of months, and wave disturbance is also a source of passive movement on a scale of 10s of centimetres (Hunt & Scheibling 1998). Similar displacement of tagged mussels (5 to 25 mm shell length) was also documented on a temperate shore, most of which moved < 5 cm and 6 individuals which moved 10 to 49 cm (Hunt & Scheibling 2002).…”
Section: Adult Displacement and Scales Of Connectivitymentioning
confidence: 83%
“…Hunt & Scheibling (1996) documented the settlement of post-larval mussels on natural substrata in a temperate system in which only 20 to 31% of colonizers measured 5 to 12 mm. In another study, most colonizers were either recruits (0.5 to 1.9 mm) or small juveniles (2 to 4.9 mm; Hunt & Scheibling 1998). An experiment using mussel transplants revealed that most colonizers were recruits < 2 mm shell length, while individuals measuring 2 to 10 mm only contributed to <15-20% of colonization (Hunt & Scheibling 2001).…”
Section: Demographic and Spatial Structure Of Mytilus Colonizationmentioning
confidence: 99%
See 2 more Smart Citations